Representation of Disabled People in the Federal Media (by the Materials of the Content Analysis) - Ya. S. Rocheva; A. L. Shavonin; A. A. Shadrin; S. V. Sheverdina (Дискурс)
Introduction. The representation of people with disabilities affects the formation of the image in the public mind. The media play a significant role in shaping the representation of people with disabilities, and this affects the assessment, perception, value judgments about people with disabilities, which for a long time were built incorrectly, stereotyped, and did not contribute to integration, and contradicted the ongoing social policy of the state. Based on the study, the authors noted the neutral nature of the presentation of materials in print media, the use of the term “disabled”, which corresponds to the human rights model of disability, and their representation through materials related to the social policy of the state and charity.Methodology and sources. The research formed on the basis of understanding sociology, structural functionalism, phenomenology and modern communication theories. The article uses the ideas of M. Weber, T. Parsons, N. Luhmann, G. Lasswell, D.P. Gavra, M. Heidegger and E. Yarskaya-Smirnova. The main research method is the qualitative content analysis of federal media articles.Results and discussion. The study made it possible to identify the dominant ideas about people with disabilities and formulate recommendations for changing the nature of the representation of disability and the image of a person with a disability. The image of a disabled person is built on the basis of a medical model of disability and stereotypes based on perception through pity, sacrifice and helplessness. The predominance of such materials in the information field could form a negative image of people with disabilities as helpless people and being a “burden” in the minds of society members. It is required to increase the number of materials in the media that tell about the achievements of people with disabilities, as well as the formation of a monitoring system that will allow monitoring the observance of the rights of people with disabilities in the media.Conclusion. Based on a comparative analysis of the author's research and materials of other authors, it was made a conclusion about the stagnation of the representation of people with disabilities in the federal media, which is a social problem. More frequent use of the image of a disabled person as an independent actor and popularization of the trend for inclusion are required to solve it. Further options for studying the representation of people with disabilities in the media are presented.